2018
DOI: 10.17509/sosietas.v8i1.12505
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Yang Melatarbelakangi Perubahan Gaya Hidup Anak Pada Keluarga Tenaga Kerja Wanita

Abstract: Didalam suatu keluarga, umumnya selalu diterapkan nilai dan norma sosial guna membentuk dan mencapai keluarga yang sejahtera. Salah satu tujuan wanita di Desa Mekarjaya memilih bekerja sebagai tenaga kerja wanita adalah agar dapat hidup lebih baik. Seperti kondisi finansial yang tidak cukup mendukung dalam kesejahteraan keluarga dan benar-benar ingin membantu suami dalam mencari nafkah serta memenuhi kebutuhan salah satunya adalah pendidikan anak. Gaya hidup anak keluarga TKW di Desa Mekarjaya berbeda dengan g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
1
0
1
Order By: Relevance
“…The results of the study found that the social environment, personality, level of motivation and level of information were very influential in shaping the lifestyle of the individual financial behavior of people of productive age in Trenggalek Regency. Where this is in line with research [12] which states that the factors underlying lifestyle come from internal factors in the form of attitudes, experiences and observations, personality, self-concept, motives and perceptions as well as external factors in the form of reference groups, family, social class and culture.…”
Section: Lifestyle Influence On Financial Behaviorsupporting
confidence: 75%
“…The results of the study found that the social environment, personality, level of motivation and level of information were very influential in shaping the lifestyle of the individual financial behavior of people of productive age in Trenggalek Regency. Where this is in line with research [12] which states that the factors underlying lifestyle come from internal factors in the form of attitudes, experiences and observations, personality, self-concept, motives and perceptions as well as external factors in the form of reference groups, family, social class and culture.…”
Section: Lifestyle Influence On Financial Behaviorsupporting
confidence: 75%
“…In terms of lifestyle, a person's nature can be measured through their attitudes towards themselves and their environment . A person's lifestyle is influenced by several factors, including internal factors encompassing attitudes, experiences and observations, personality, self-concept, motives, and perceptions, and external factors encompassing reference groups, family, social class, and culture (Priansa & Suryawardani, 2020;Wahyuni & Ruyadi, 2018).…”
Section: Lifestylementioning
confidence: 99%
“…Perubahan gaya hidup yang dirasakan oleh informan sebagai pengguna layanan Netflix dipengaruhi oleh dua faktor yaitu faktor yang berasal dari diri individu (internal) dan faktor yang berasal dari luar (eksternal) seperti yang diungkapkan oleh Nugraheni dalam Wahyuni dan Ruyadi 13 , dimana yang masuk kedalam faktor internal adalah sikap, pengalaman dan pengamatan, kepribadian, konsep diri, motif, dan persepsi, sedangkan untuk faktor eksternal adalah kelompok referensi, keluarga, kelas sosial dan kebudayaan. Faktor internal sikap adalah suatu keadaan jiwa dan keadaan pikiran yang dipersiapkan untuk memberikan tanggapan terhadap suatu objek yang diorganisasi melalui pengalaman dan mempengaruhi secara langsung pada perilaku.…”
Section: Hasil Dan Pembahasanunclassified